ANALISIS PUTUSAN MAHKAMAH SYARI’AH PROVINSI ACEH DALAM KASUS PEMBATALAN HIBAH ( Studi Putusan Mahkamah Syari’ah Provinsi Aceh Nomor 28/PDT-G/2015/MS-Aceh ) - TEUKU HENDRA YUSNANDAR (PREMISE LAW JURNAL, 2016)
Hibah is a part or all of someone’s property given to his heir, friends, or other people before he dies. A conditional hibah occurs when it is related to a requirement such a requirement of the limitation of using it by the giver to the receiver so that it becomes invalid. A withdrawal of something which has already been given (hibah) is illegal although the hibah is between sibling or husband and wife. Hibah can only be withdrawn when it is given by parents to their children. The research used judicial normative and descriptive analytic. The implementation of conditional hibah in the people of Banda Aceh has been their own tradition even though there is no regulation on it, Therefore, the judge hands down the verdict outside of the lawsuit because conditional hibah is not regulated in law so that the judge considers that the withdrawal of hibah given by parents to their children is permitted in the KHI. Keywords: Hibah, Conditional Hibah, Hibah Revocation